Search and the development of the economics of information - Lippman, Steven (Estudios de Economía, 2016)
In this paper we trace the evolution of economic search theory and the concomitant accumulation of insights so as to elucidate is successes as well as its central location within the economics of information. The reason for the phenomenal success of search theory is twofold. First, Stigler’s fixed sample search was the first entrant in the literature to explicity model the acquisition of information.